Bifunctional lanthanum phosphate substrates as novel adsorbents and biocatalyst supports for perchlorate removal - Sankar, S.; Prajeesh, G.; Anupama, V.; Krishnakumar, B.; Hareesh, P.; Nair, Balagopal; Warrier, K.; Hareesh, U. (Elsevier BV, 2014)
Porous lanthanum phosphate substrates, obtained by an environmentally benign colloidal forming process employing methyl cellulose, are reported here as excellent adsorbents of perchlorate with >98% efficiency and with 100% reusability. Additionally, the effectiveness of such substrates as biocatalyst supports that facilitate biofilm formation of perchlorate reducing microbes (Serratia marcescens NIIST 5) is also demonstrated for the first time. The adsorption of perchlorate ions is attributed to the pore structure of lanthanum phosphate substrate and the microbial attachment is primarily ascribed to its intrinsic hydrophobic property. Lanthanum phosphate thus emerges as a dual functional material that possesses an integrated adsorption/bioremediation property for the effective removal of ClO4- which is an increasingly important environmental contaminant. © 2014 Elsevier B.V.